Effect of different regions on fermentation profiles, microbial communities, and their metabolomic pathways and properties in Italian ryegrass silage - Fu, Zhihui; Sun, Lin; Wang, ZhiJun; Liu, Yichao; Hao, Junfeng; Gao, Cuiping; Ge, Gentu (Frontiers in Microbiology, 2023)
Introduction Italian ryegrass is less studied in northern China due to high-quality forage grass has not been fully utilized. Full utilization of high-quality forage grass helps to alleviate the shortage of forage grass in winter and spring season and guarantee stable development of livestock production. Consequently, this study was aimed to evaluate the effects of different regions in northern China on the fermentative products, bacterial community compositions, and metabolic pathways and metabolites of Italian ryegrass silage. Methods The Italian ryegrass was harvested from three regions (Ordos-WK; Hohhot-AK; Ulanqab-SYK) and ensiled for 60 days. Single molecule real-time (SMRT) sequencing and ultra-high performance liquid chromatography-mass spectrometry (UHPLC–MS/MS) were used to analyze bacterial communities and metabolites, respectively. Results After 60 d of fermentation, the SYK group had the lowest pH (4.67), the highest lactic acid contents (95.02 g/kg DM) and largest lactic acid bacteria populations (6.66 log10 cfu/g FM) among the treatment groups. In addition, the SYK group had the highest abundance of Lactiplantibacillus plantarum (63.98%). In SYK group, isoquinoline alkaloid biosynthesis was the significantly enriched (p < 0.05) and high-impact value (0.0225) metabolic pathway. In AK group, tryptophan metabolism the was the significantly enriched (p < 0.001) and high-impact value (0.1387) metabolic pathway. In WK group, citrate cycle (TCA cycle) was the significantly enriched (p < 0.001) and high-impact value (0.1174) metabolic pathway. Further, Lactiplantibacillus plantarum was positively correlated with cinnamic acid, tetranor 12-HETE, D-Mannitol, (2S)-2-amino-4-methylpentanoic acid L-Leucine, guanine, isoleucyl-aspartate and 3,4-Dihydroxyphenyl propanoate, but negatively correlated with isocitrate and D-mannose. Discussion In conclusion, this study can improve our understanding of the ensiling microbiology and metabolomics in different regions to further regulate the fermentation products and promote livestock production.